Developing an Enterprise Risk Management Roadmap for the Passenger Rail Agency of South Africa - Mangcu, T.; Hassan, F.S.; Grobbelaar, S. (South African Journal of Industrial Engineering, 2025)
This research explored the development of an enterprise risk management (ERM) roadmap for the Passenger Rail Agency of South Africa (PRASA) amid growing business risks from global financial shifts and pandemics. It emphasised a holistic management approach to address PRASA’s ERM difficulties and opportunities. It also advocated a tailor-made ERM roadmap underpinned by an action priority matrix. Given the lack of ERM literature for public enterprises, this study aimed to bridge that gap using a mixed-methods approach to identify barriers, enablers, and opportunities for ERM implementation. The findings suggested that a customised ERM roadmap would enhance PRASA’s governance, efficiency, risk, and resilience, and contribute to value creation.